Modulating long‐range energetics via helix stabilization: A case study using T4 lysozyme - Rosemond, Sabriya N. (Protein Sci, 2018)
Cooperative protein folding requires distant regions of a protein to interact and provide mutual stabilization. The mechanism of this long‐distance coupling remains poorly understood. Here, we use T4 lysozyme (T4L*) as a model to investigate long‐range communications across two subdomains of a globular protein. T4L* is composed of two structurally distinct subdomains, although it behaves in a two‐state manner at equilibrium. The subdomains of T4L* are connected via two topological connections: the N‐terminal helix that is structurally part of the C‐terminal subdomain (the A‐helix) and a long helix that spans both subdomains (the C‐helix). To understand the role that the C‐helix plays in cooperative folding, we analyzed a circularly permuted version of T4L* (CP13*), whose subdomains are connected only by the C‐helix. We demonstrate that when isolated as individual fragments, both subdomains of CP13* can fold autonomously into marginally stable conformations. The energetics of the N‐terminal subdomain depend on the formation of a salt bridge known to be important for stability in the full‐length protein. We show that the energetic contribution of the salt bridge to the stability of the N‐terminal fragment increases when the C‐helix is stabilized, such as occurs upon folding of the C‐terminal subdomain. These results suggest a model where long‐range energetic coupling is mediated by helix stabilization and not specific tertiary interactions.